Kedudukan Akta Ikrar Wakaf Saham sebagai Upaya untuk Menjamin Kepastian Hukum dalam Peralihan Saham Melalui Wakaf - Mustafa; Lastuti Abubakar; Elis Nurhayati (Jurnal Hukum Lex Generalis, 2025)
Waqf is a financial and social instrument in Islam that has significant purposes and functions. The purpose of waqf is for promote public welfare according to the potential and economic benefits of waqf assets, one of which is stock waqf. To achieve the objectives of share waqf, legal certainty is needed to ensure that the transfer of shares through waqf can be carried out in accordance with the will of the waqif. Shares that can be endowed are shares from companies whose business activities do not conflict with sharia principles. Waqf shares must be set out in a Deed of Pledge of Waqf which will then be submitted to the Board of Directors, if it is a closed company, or to an investment institution if the waqf shares are listed on the stock exchange. It is this Deed of Pledge of Waqf that guarantees legal certainty and becomes the basis for transferring the rights to the shares into the name of the nazhir.